Invasive and Non-invasive Stimulation of the Obese Human Brain - Pleger, Burkhard (Frontiers in Neuroscience, 2018)
Accumulating evidence suggests that non-invasive and invasive brain stimulation may reduce food craving and calorie consumption rendering these techniques potential treatment options for obesity. Non-invasive transcranial direct current stimulation (tDCS) or repetitive transcranial magnet stimulation (rTMS) are used to modulate activity in superficially located executive control regions, such as the dorsolateral prefrontal cortex (DLPFC). Modulation of the DLPFC’s activity may alter executive functioning and evoke remote effects in reward-related dopamine-rich regions such as the striatum or orbitofrontal cortex. Modulation of food reward processing can also be achieved by invasive deep brain stimulation (DBS) targeting the nucleus accumbens. Another potential target for TBS is the lateral hypothalamic area potentially leading to improved energy expenditure. To date, available evidence is however restricted to few exceptional cases of morbid obesity. The vagal nerve plays a crucial role in signaling the homeostatic demand to the brain. Invasive or non-invasive vagal nerve stimulation (VNS) is thus assumed to reduce appetite, rendering VNS another possible treatment option for obesity. Based on currently available evidence, the U.S. Food and Drug Administration recently approved invasive VNS for the treatment of obesity. This review summarizes available scientific evidence regarding these techniques’ efficacy in modulation food craving and calorie intake. It is time for large controlled clinical trials that are necessary to translate currently available research discoveries into patient care.